Consumers’ Intention on Rooftop PV Adoption to Promote Renewable Energy using Extended UTAUT Model in Indonesia - Eliva, Najwa; Nurcahyo, Rahmat; Habiburrahman, Muhammad; Lianto, Benny (International Journal of Sustainable Energy Planning and Management, 2025)
To address air pollution and reduce dependence on fossil fuels, the Indonesian government has set a target to achieve net zero emissions by 2060 through the acceleration of new and renewable energy utilization. Among various technologies, rooftop photovoltaic (PV) systems are considered highly viable, particularly for the residential sector, which accounts for 43% of national electricity consumption. However, despite their potential, rooftop PV adoption in Indonesia remains underdeveloped, primarily due to low consumer intention and negative public perception. This study examines consumer perspectives on rooftop PV adoption. An extended Unified Theory of Acceptance and Use of Technology (UTAUT) framework is utilized, incorporating Knowledge and Perceived Cost as additional factors. Spearman’s correlation analysis is employed to assess the significance and relationships among key factors. The findings indicate that the majority of respondents demonstrate a moderate to high intention to adopt rooftop PV. Perceived Cost emerges as the most significant factor influencing adoption, emphasizing the high investment costs associated with renewable energy technology. Other influential factors include Facilitating Conditions, Social Influence, Effort Expectancy, Performance Expectancy, and Knowledge. These insights provide empirical guidance for policymakers and industry stakeholders in designing strategies to enhance rooftop PV adoption and support Indonesia’s transition towards sustainable energy.